Association between severity of obstructive sleep apnea and number and sites of upper airway operations with surgery complications - Asha'ari, Zamzil Amin; Ab Rahman, Jamalludin; Mohamed, Abdul Hadi; Abdullah, Kahairi; Leman, Wan Ishlah (American Medical Association, 2017)
IMPORTANCE :In patients with obstructive sleep apnea (OSA), operative risks depend on the severity of the underlying OSA and the invasiveness of the surgical procedure. OBJECTIVE: To investigate the nature of the associations between the severity of OSA and the number and anatomical sites of upper airway operations with operative complications. DESIGN, SETTING, AND PARTICIPANTS: This retrospective study included adult patients diagnosed with OSA (apnea-hypopnea index [AHI], >5) who underwent upper airway surgery at a single tertiary referral hospital between October 1, 2008, and October 1, 2015. INTERVENTIONS: All patients underwent single or combination surgery on the nose, palatopharyngeal (tonsils, adenoids, and soft palate), and tongue base as a treatment of OSA. MAIN OUTCOMES AND MEASURES: Pulmonary, surgical, and cardiovascular complications within the first 30 postoperative days were analyzed according to OSA severity and types of upper airway surgery. Logistic regression was used to assess the multivariable association of OSA, age, sex, body mass index, medical comorbidities, and types of upper airway surgery with short-term operative complications. RESULTS: The study included 95 patients (87 males [91.6%]; 83 were Malay [87.4%]; mean [SD] age, 37.7 [1.6] years) with complete data and follow-up who underwent upper airway surgery to treat OSA. Patients with more severe OSA had greater body mass index (Cohen d, 0.27; 95% CI, -0.28 to 0.82), longer surgical time (Cohen d, 1.57; 95% CI, 0.95-2.15), and older age (Cohen d, 3.06; 95% CI, 2.29-3.77). At least 1 operative complication occurred in 48 of 95 patients (51%). In a multivariable model, the overall complication rate was increased with age and body mass index. Complication rates were not associated with AHI severity, type of procedure performed, and whether the surgery was single or combination surgery. Lowest oxygen desaturation (odds ratio, 1.03; 95% CI, 0.96-1.45; P = .04) and longest apnea duration (odds ratio, 1.03; 95% CI, 0.99-1.08; P = .02) were polysomnographic variables that predict the short-term operative complications. CONCLUSIONS AND RELEVANCE: In patients with OSA undergoing upper airway surgery, the severity of OSA as assessed by AHI, and the sites and numbers of concurrent operations performed were not associated with the rate of short-term operative complications.